Communications and Industrial Mission - Stetter, Max (Communicatio socialis, 1982)
My involvement in pastoral work in a new industrial parish on the outskirts of Thika had very little to do with the communication skills I had acquired in a number of courses over the years. In the workers' housing estates where there is no electricity, the electronic era is delayed. (...)